2013
DOI: 10.5966/sctm.2013-0072
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Differentiation Factors by Mesoporous Silica Particles Assists Advanced Differentiation of Transplanted Murine Embryonic Stem Cells

Abstract: Stem cell transplantation holds great hope for the replacement of damaged cells in the nervous system. However, poor long-term survival after transplantation and insufficiently robust differentiation of stem cells into specialized cell types in vivo remain major obstacles for clinical application. Here, we report the development of a novel technological approach for the local delivery of exogenous trophic factor mimetics to transplanted cells using specifically designed silica nanoporous particles. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Gliafin (153-ETMYDKILKNLSRSR-167; UniProtKB entry no. Q07731) is a small peptide that displays GDNFlike activity and was recently demonstrated to induce efficient differentiation and functional integration of transplanted stem cell derivatives [81]. It has not been tested yet as an alternative to GDNF in local delivery experimental paradigms of inflammatory or neuropathic pain, but it deserves further attention as a possible GDNF therapeutic substitute.…”
Section: Gfl Mimetics and Small Molecules Targeting The Gfls' Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gliafin (153-ETMYDKILKNLSRSR-167; UniProtKB entry no. Q07731) is a small peptide that displays GDNFlike activity and was recently demonstrated to induce efficient differentiation and functional integration of transplanted stem cell derivatives [81]. It has not been tested yet as an alternative to GDNF in local delivery experimental paradigms of inflammatory or neuropathic pain, but it deserves further attention as a possible GDNF therapeutic substitute.…”
Section: Gfl Mimetics and Small Molecules Targeting The Gfls' Receptorsmentioning
confidence: 99%
“…Based on the previously discussed evidence of animal studies, and considering that GDNF has been demonstrated to undergo both retrograde and anterograde transport in neurons [10,31] it seems reasonable that, broadly-speaking, a GDNF-related therapy may be effective at both peripheral and central levels. In addition, as minimally invasive topical or systemic routes of administration other than the direct delivery into the central or the peripheral neurons have proved to be efficacious in animal models [4,64,[81][82][83], it seems desirable that these routes are explored in clinical settings too.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Moreover, nanoporous MSPs hold the potential to be not only a very efficient but also a cost effective drug delivery system. We previously showed that MSPs loaded with growth factor mimetics promote survival and differentiation of co-implanted neural stem cells, 7 indicating that the MSP delivery system can serve as a valuable tool for controlling differentiation of transplanted stem cells. Toxicological data from in vitro and in vivo studies suggest that unloaded MSPs have no observable harmful effects and are well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…53,66,134 MSNs undergo endocytosis in cells, including MSCs, with no adverse effect on differentiation, viability, and proliferation. 33 The large pore volume and surface area allows for nucleic acid, peptides, and polymers to be adsorbed, trapped, or bound.…”
Section: Silica-based Particlesmentioning
confidence: 99%